Corporate innovation strategies : corporate social responsibility and shared value creation - Gasmi, Nacer (Innovation, entrepreneurship, management series. Smart innovation set, 2021)
This book presents a theoretical development that analyzes the challenges of CSR strategies based on the creation of shared value. --